PENGARUH SUBSTITUSI TEPUNG UBI JALAR UNGU TERHADAP KUALITAS PUTU AYU - Sukiyaki, Lamtiur Ester; Gusnita, Wiwik; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
The use of purple sweet potato flour is not optimalyet, either on the diversification of food processing, while the purple sweet potato flour can be an alternative to replace part of the flour as the main ingredient of putu ayu. This study aimed to analyze the influence of flour substitution purple sweet potato as much as 20%, 40%, 60% of the quality form the best results X1 (20%), the volume of the best results X1 (20%), the color best results X3 (60%), aroma X3 best results (60%), taste the best results X3 (60%), X1 texture best results (20%) on putu ayu. This type of research is experimental method completely randomized design using three repetitions. The instrument used was a questionnaire which is then analyzed by the organoleptic test by testing levels and using a Likert scale, and to test the hypothesis using statistical ANOVA followed by Duncan test. Based on the results of the study showed that overall the best value contained in the purple sweet potato flour substitution as much as 20% (X1).Keywords: Substitution, Purple Sweet Potato Flour, Putu Ayu, Quality1Prodi Pendidikan